PERANCANGAN SISTEM INFORMASI PURCHASE ORDER ATK PADA PT. INTEGRASI PRODUKTIVITAS INDONESIA BERBASIS WEB - Ofah Musyarrofah; Tubagus Mochamad Isnaeni; Diah Anggraini Fitri; Nurul Hikmah (Journal of Innovation And Future Technology, 2025)
The advancement of technology has made it easier for people to conduct transactions online. PT Integrasi Produktivitas Indonesia is a newly established startup operating in the manufacturing and service sectors, specifically in organizing seminars and bootcamp training programs aimed at equipping students with skills aligned with industry standards. Within the company, the purchasing staff is responsible for procuring office supplies (ATK), and the process involves using a Purchase Order (PO) as a proof of transaction. However, the current PO system is not yet computerized, leading to inefficient document storage, time-consuming data retrieval, and increased risk of permanent data loss. This study aims to facilitate the PO creation process for purchasing staff and streamline item requests by the General Affairs (GA) department through the development of a Web-based information system. The system is developed using the Waterfall methodology, which includes analysis, design, coding, testing, and maintenance phases. The design tools used include flowcharts, context diagrams, Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), normalization, table relationships, file structures, and user interface design. The system is built using PHP programming language and MySQL as the database. Based on black-box testing, all system functions, particularly button features, operate as expected.